Republic of Uzbekistan : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Uzbekistan. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Uzbekistan's external position remains strong. External shocks, which began in 2014, lowered exports, commodity prices, and remittances and contributed to a decline in growth from about 8 percent to 5 percent in 2017. Growth of domestic employment remained below one percent. A loosening of fiscal and monetary policies, along with price and foreign exchange liberalization, caused inflation to pick up in late 2017 and was close to 20 percent in early 2018. International reserves were equivalent to 19 months of imports of goods and services at end-2017 and debt is low. GDP is projected to expand by about 5 percent in 2018-19, but domestic job creation will continue to lag.